1996
DOI: 10.1097/00005537-199601000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem Auditory Evoked Potentials in Patients With Ischemic Heart Disease

Abstract: The authors of this study used the method of increased stimulus rate on brainstem auditory evoked potentials (BAEPs) in 30 patients with ischemic heart disease (IHD) and in an equal number of healthy age-matched control subjects. The BAEPs were recorded using 100- to 3000-Hz alternating polarity clicks at a rate of 22.6 per second. Measurements included the absolute latencies of waves I through V, the interpeak latencies I-III, III-V, and I-V, and the peak amplitudes of peaks I, III, and V. The measured absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
1
6
0
1
Order By: Relevance
“…If primary auditory and somatosensory cortices are part of a functional network (van de Ven et al 2009), then perhaps anatomical changes in one region could impact another region in the network (Oh et al 2011). In addition, extratemporal and temporal lobe findings may reflect comorbid factors such as vascular disease that have widespread aging effects on the peripheral auditory system (Gates et al 1993;Thomopoulos et al 1997;Torre et al 2005;Liew et al 2007;Helzner et al 2011;although see Parving et al 1993;Karamitsos et al 1996) and the brain (Eckert 2011). Influences of vessel disease on hearing in females (Gates et al 1993;Helzner et al 2011) could also explain the association between gray matter in the left Te1.2 region and low frequency hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…If primary auditory and somatosensory cortices are part of a functional network (van de Ven et al 2009), then perhaps anatomical changes in one region could impact another region in the network (Oh et al 2011). In addition, extratemporal and temporal lobe findings may reflect comorbid factors such as vascular disease that have widespread aging effects on the peripheral auditory system (Gates et al 1993;Thomopoulos et al 1997;Torre et al 2005;Liew et al 2007;Helzner et al 2011;although see Parving et al 1993;Karamitsos et al 1996) and the brain (Eckert 2011). Influences of vessel disease on hearing in females (Gates et al 1993;Helzner et al 2011) could also explain the association between gray matter in the left Te1.2 region and low frequency hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The women with histories of stroke and overall CVD also were twice as likely to have high-frequency hearing losses as women without CVD. Moreover, there are a substantive number of studies that have not found any relationship between hearing loss and CVD or with CVD risk factors (Bunch, 1931; Karamitsos et al, 1996; Parving, Hein, Suadicani, Ostri, & Gyntelberg, 1993). …”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular dysfunction and prolongation of BAEPs were usually accompanied by a reduction of cerebral blood flow, leading subjects to loss of consciousness and even death of the patient. [23] Sensory derangement, particularly of pain threshold in experimental animals and impairments in sensory conduction in human beings has also been reported in hypertension.…”
Section: Discussionmentioning
confidence: 99%